Prospección arqueológica de una laguna de altura (Busa), cantón San Fernando - Yépez, Alden (2010)
The processes of human occupation in the head of the Jubones river, in the ecuadorian region of austro, were probably subjected to heavy climatic variations provoked by the El Niño phenomenon along the ecuadorian coast. An archeological survey and underwater exploration were carried out in the Busa lagoon, San Fernando county, Azuay, during the summer of 2009. The lagoon is located at 2.800 meters in the river valley of the Jubones river. archeological investigation revealed two periods of occupation: one pre-hispanic, possibly a formative component, and one colonial (most likely early colonial). The pre-hispanic material evidence in the interior of the lagoon is eye-catching as an indicator of the climate changes provoked by the El Niño phenomenon, those same changes which determined the rising and falling of the levels of water in the lagoon. The oral tradition of the inhabitants of Busa partially reflects these climate changes. The discovery of rock-covered tombs around the lagoon indicates that this place had sacred connotations for the aboriginals. Los procesos de ocupación humana prehispánica en la cabecera del río jubones, en el austro ecuatoriano, probablemente estuvieron sujetos a las fuertes variaciones climáticas provocadas por el fenómeno de El Niño en las costas ecuatorianas. Una prospección arqueológica y una exploración subacuática se realizaron en la laguna de Busa, cantón San Fernando, Azuay durante el verano del 2009. La laguna se ubica a 2.800 msnm en las cabeceras del valle del río jubones. Las investigaciones arqueológicas revelaron dos períodos de ocupaciones: uno prehispánico, posiblemente con un componente formativo, y uno colonial probablemente temprano. La evidencia de material cultural prehispánico al interior de la laguna es llamativa como indicador de los cambios climáticos provocados por el fenómeno de El Niño, los mismos que determinaran el crecimiento y decrecimiento del nivel de agua de la laguna. La tradición oral de los moradores de Busa refleja en parte estos los cambios ...